Experience with Serum Magnesium Estimations in Critically Ill Patients Admitted in High Dependency Unit of A Tertiary Care Hospital (Bangladesh Journal of Medicine, 2018)
Background: Magnesium deficiency has been a common, but easily ignored, electrolyte abnormality. Studies on magnesium in our country are lacking. Here, we have estimated and correlated serum magnesium levels with outcomes and other electrolyte imbalance in critically ill patients with respect to the mortality, in hospital outcome and length of high dependency unit (HDU) stay.Methods: A prospective, observational study was conducted in patients who had been admitted to the HDU. Patient’s demographic profile, medical history, serum magnesium, calcium and electrolytes were enrolled on admission. Patients were divided into normomagnesemic, hypomagnesemic hypermagnesemic groups and compared for various parameters.Results: Out of 60 critically ill-patients, 32 patients (53.33%) were hypomagnesemic, 20 patients (33.33%) were normomagnesemic and 8 patients (13.33%) were hypermagnesemic. The duration of stay of the patients in HDU, in hospital outcome and mortality showed significant variation between these groups. Associated electrolyte abnormalities in hypomagnesemic patients were hypokalemia (56.25%) and hypocalcemia (62.50%). Most of the hypomagnesemic patients were hypertensive (62.50% vs 40%) and was presented in drowsy state (50% vs 40%) compared to normomagnesemic group. Mortality of hypomagnesemic group was 37.50% while that of hypermagnesemic group was 25%. In hospital, arrythmia (18.75%) and convulsion (12.50%) developed in hypomagnesemic groups. Mean duration of length of stay in HDU was 7.45 days in hypomagnesemic, 6.83 days normomagnesemic, and 8.67 days in hypermagnesemic group.Conclusion: Development of magnesium imbalance in critically ill patients is associated with bad prognosis. Monitoring of serum magnesium levels may have prognostic, perhaps therapeutic implication.Bangladesh J Medicine Jul 2018; 29(2) : 69-74